The observation of spin Seebeck effect in opposite spin Hall angle materials of polycrystalline bulk-Fe3O4/(Co/Fe) systems - Ruchipas Bavontaweepanya; Yingyot Infahsaeng; Ekkarat Pongophas; Wasan Maiaugree; Piyawat Piyasin; Dulyawich Palaporn; Likkhasit Wannasen; Supree Pinitsoontorn; Rungrueang Pattanakul; Harihara Ramamoorthy; Ratchanok Somphonsane; Paowarin Khayaiwong; et al. (AIP Advances, 2022)
In this study, we report on the observation of spin current in opposite spin Hall angle materials of polycrystalline bulk-Fe3O4/Co and polycrystalline bulk-Fe3O4/Fe spin Seebeck effect (SSE) devices. In contrast to prior works, a facile and low-cost hot-pressing powder metallurgy process was employed to manufacture the polycrystalline bulk-Fe3O4 samples. The crystal structure, magnetization properties, and electrical resistivity characterizations of the fabricated bulk-Fe3O4, which were performed using x-ray diffraction, vibration sample microscope, and four-point probe, respectively, revealed excellent agreement with those of conventional Fe3O4. By taking advantage of the fact that the SSE signal in our devices is typically contaminated with the anomalous Nernst effect (ANE), we show that the total thermo-voltage obtained from our devices can be enhanced by the significant ANE signals exhibited by the Co and Fe spin detectors. Importantly, the ANE contributions could be filtered out from the main signal by independent measurements of the ANE voltage in SiO2/Co and SiO2/Fe systems, thereby allowing the approximate extraction of the SSE voltage. Our experiments reveal that the polarity of the measured ANE (and pure SSE voltages) are opposite to each other in the bulk-Fe3O4/Co and bulk-Fe3O4/Fe structures, thus proving the opposite spin-hall angles character of these materials. The findings of this work provide a pathway for further exploration of methods through which the thermo-voltage output in future spin-Hall thermopile devices may be improved using materials manufactured via a facile, low-cost, and easily scalable process.
Keywords: Magnetic properties of thin films; Quantum and electron transport phenomena; Magneto-Optical Properties and Applications